Prognosis of autoimmune hepatitis showing acute presentation. Issue 6 (22nd October 2012) - Yamamoto, Kazuhide; Miyake, Yasuhiro; Ohira, Hiromasa; Suzuki, Yoshiyuki; Zeniya, Mikio; Onji, Morikazu; Tsubouchi, Hirohito
<x xml:space="preserve">Abstract</x> Aim The number of patients with autoimmune hepatitis (AIH) showing acute presentation has increased. This study aimed to assess their prognosis. Methods A survey of AIH patients by sending questionnaires was performed, and 96 patients showing acute presentation were investigated. Results The median age was 58 years and 78 patients (81%) were female. Eighty‐four patients (88%) were positive for antinuclear antibody and/or anti‐smooth muscle antibody. The median serum immunoglobulin G level was 2252 mg/dL. Twenty‐five patients (26%) showed histological acute hepatitis. As initial treatment, 88 patients (92%) were treated with corticosteroid, and 28 of them received pulse steroid treatment. Overall, 11 patients (11%) reached fatal outcomes (nine death and two liver transplantation). Patients with histological acute hepatitis showed higher serum bilirubin levels, lower prothrombin activities and higher prothrombin time–international normalized ratios (PT‐INR) and reached fatal outcomes more frequently. With a multivariate logistic regression analysis, prothrombin activity and PT‐INR at presentation was associated with fatal outcomes. Nine of 13 patients (69%) showing prothrombin activity of 40% or lower at presentation and nine of 19 patients (47%) showing PT‐INR of 1.5 or higher reached fatal outcomes. Furthermore, of 13 patients showing prothrombin activity of 40% or lower and/or PT‐INR of 1.5 or higher at presentation who were treated with pulse steroid treatment, four (31%) died from infectious disease.1 Conclusion Prothrombin activity and PT‐INR are prognostic factors for AIH showing acute presentation. Physicians should pay attention to the development of infectious disease when pulse steroid treatment is performed.1